Assessment of Microplastic Pollution in Selected Water Bodies in Rivers State, Nigeria - J. S. Attah; H. O. Stanley; F. D. Sikoki; O. M. Immanuel (Archives of Current Research International, 2023)
This study aimed to assess of microplastic pollution in selected water bodies in River State, Nigeria. Two water bodies, one fresh water (New Calabar River) and one estuary (Bonny River) were sampled in the present study for presence of microplastics in water, sediment and fish samples in the aquatic milieu. Microplastics were extracted using standard methods and were characterized using GCMS. Four plastic types namely polyethylene, polyethylene terephthalate, polystyrene, polypropylene was detected in all samples. Likewise, four plasticizers namely dioctyl terephthalates, polybrominated diphenyl ether, acrylic fibre and tetrabromobisphenol A were all detected in sediment, water and fish samples from Bonny River and New Calabar River. FTIR analysis of microplastics showed patterns typical of polystyrene. This study has shown that water, sediment and fish samples contain microplastics. This is a worrisome development as the water are used for domestic purposes among persons resident along the water courses and the fish species sampled is commonly available as source of protein for majority of persons. This calls for greater enlightenment on the possible danger of microplastics pollution in the study area and for measures to check macroplastics pollution, which bring about microplastics pollution in the aquatic environment. Such measures should include promotion of the use of plant material as food wrappings and to dissuade dumping of solid waste in the rivers.